Rietveld refinement, microstructure, conductivity and impedance properties of Ba[Zr0.25Ti0.75]O-3 ceramic - Badapanda, T.; Senthil, V.; Rout, S. K.; Cavalcante, L. S. [UNESP]; Simões, Alexandre Zirpoli [UNESP]; Sinha, T. P.; Panigrahi, S.; de Jesus, M. M.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2011)
In this work, we report the Rietveld refinement, microstructure, conductivity and impedance properties of Ba[Zr0.25Ti0.75]O-3 ceramic synthesized by solid state reaction. This ceramic was characterized by X-ray diffraction, Rietveld refinement, scanning electron microscopy and energy dispersive X-ray spectrometry. Impedance spectroscopy analyses reveals a non-Debye relaxation phenomenon being its relaxation frequency moving toward to positive side with increase of temperature. A significant shift in impedance loss peaks toward higher frequency side indicates conduction in material and favoring the long range motion of mobile charge carriers. The frequency dependent ac conductivity at different temperatures indicates that the conduction process is thermally activated. The variation of dc conductivity exhibited a negative temperature coefficient of resistance behavior. The ac conductivity data are used to evaluate the density of states at Fermi level and activation energy of this ceramic. The dc electrical and thermal conductivities of grain and grain boundary have been discussed. (C) 2011 Elsevier B.V. All rights reserved. 3
Keywords: Solid state reaction; Grain boundaries; Impedance; Perovskites